Oral cavity health and remedy options to stimulate epithelization of oral mucosa - Boitsaniuk, Svitlana; Chorniy, Sofiia; Manashchuk, Nadia; Chornij, Natalia; Pohoretska, Khrystyna; Patskan, Lyudmula; Levkiv, Mariana (Journal of Education, Health and Sport, 2023)
Oral mucosa is an inner lining of oral cavity, which maintains different functions including protection of epithelial integrity. Pathology of oral mucosa can develop in response to the action of pathogenic microorganisms, viruses, and various traumatic factors; it can be a result of systemic pathology of a patient as well. Pain and discomfort usually accompanies such conditions leading to decrease of patient wellbeing. The basis of the pharmacological regulation of the regeneration process is the stimulation of wound healing. The aim is to summarize and discuss the spectrum of remedy options that are used to stimulate epithelization of oral mucosa. The overall goal of the paper is to provide full and comprehensive information for dentists and their patients about medicament variety, ways of theirs application and dosage. Methods. Relevant literature from MEDLINE (PubMed), Google Scholar, and in open access journals which are published by Elsevier was selected using the following key words «oral mucosa», «epithelization», and «remedy» were used in various combinations by the year of 2023. In total there were found 48 papers. To the selected scientific papers we applied the inclusion and exclusion criteria to choose the relevant ones. Conclusions. A significant number of drugs for the treatment of inflammatory processes in the oral cavity are available nowadays on dental market. Numerous studies substantiates the effectiveness of their use in dentistry. Therefore, when choosing pharmacological drugs, preference is given to drugs with a complex effect, which locally affect various links of the pathogenetic mechanism of the occurrence of diseases and do not disturb human wellbeing.